(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Pathological tooth mobility associated with acute and chronic dental trauma represents a significant clinical risk, as it may result in disruption of the neurovascular bundle and subsequent pulp necrosis, thereby necessitating timely diagnosis and appropriate therapeutic intervention. This study investigated the clinical characteristics of mobile teeth in a cohort of 220 patients presenting with acute or chronic dental trauma. Following standard diagnostic procedures, the degree of tooth mobility was assessed in conjunction with electrodontometry and thermal sensitivity testing.